Studies on the Chemistry Control of Some Selected Drinking and Industrial Waters (Biological Sciences - PJSIR, 2005)
Water is abundantly used in heat exchangers and boilers. Water chemistry control is necessary to avoid corrosion and scaling in industrial water and health hazards in drinking water. Water used in different types of boilers has been analysed and its impact on corrosion and scaling has been discussed. Treated and untreated water samples used in heat exchangers have been analysed and their advantages and disadvantages have been discussed. Heavy and toxic metals in water sources from Rawalpindi-Islamabad area, Pakistan, have been analysed and results are reported and discussed. Water samples of primary and secondary systems of nuclear reactors have been analysed and discussed. Deposits and cruds formed in boilers and heat exchangers have been analysed and reported.